(3GdCQHYhf MOjKG aj eHGfi GdGSdGe hbhGYO GdGMcGes - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s ((3UGdM Hf GdUOjb GdfeGQi GdCfUGQi GdCTYQi s)
(3ChdgG (B:s
(3CNHQfi HLejY cJGH Gdfhhj ai eHGfj GdESdGe hbhGYO GdCMcGe ddEeGe eMjj GdOjf jMji GHf TQa Gdfhhj QMeg Gddg GdTjN GdMGaX GdeSfO CHh gQjQI YHO GdQMef Hf Ydj GdOjHY GdTjHGfj bQGAI efi Ydjg dLejYg s
(3BNQgG (B:s
(3aUd GYde Cf eYfi GdMOjK GdePchQ ChdG (B: "(3ef MaX Ydi CeJi CQHYjf hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH hgh MSHfG hfYe Gdhcjd hdG Mhd hdG bhI EdG HGddg GdYdj GdYXje s
(3Vef eLehY , JQJjHgG (B: (3ef U (B124 - (3U(B134s
(3CdMb GdeDda aj BNQgG hQbJjf TQkMG dHYV GdCdaGX GdeTcdI GdJj hQOJ aj GdCMGOjKs
(3GdfSNI HgG MhGTs
(3HGdfSNI GVWQGH aj JQJjH BNQgGs
(3cJHJ GdYfhGfGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdMOjK h GdeUWdMs